2017
DOI: 10.1371/journal.pone.0170284
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Contraceptive Adoption, Continuation, and Switching after Delivery among Malawian Women

Abstract: Women who report use of postpartum family planning may not continue their initial method or use it consistently. Understanding the patterns of method uptake, discontinuation, and switching among women after delivery is important to promote uptake and continuation of effective methods of contraception. This is a secondary analysis of 634 Malawian women enrolled into a prospective cohort study after delivery. They completed baseline surveys upon enrollment and follow-up telephone surveys 3, 6, and 12 months post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 15 publications
2
19
5
2
Order By: Relevance
“…The nding was in line with the study conducted in Egypt 46% [20]. This nding was lower as compared with those studies conducted in Vietnam 80 % [21] Malawian 58% [9], Zambia 89% [10], and Vietnam 66.7% [22]. The possible justi cation might be due to the fact that Ethiopian government has given more emphasis for LACM use, through nurses, midwives and health extension programs even at lower level of the health care system (primary health care unit).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The nding was in line with the study conducted in Egypt 46% [20]. This nding was lower as compared with those studies conducted in Vietnam 80 % [21] Malawian 58% [9], Zambia 89% [10], and Vietnam 66.7% [22]. The possible justi cation might be due to the fact that Ethiopian government has given more emphasis for LACM use, through nurses, midwives and health extension programs even at lower level of the health care system (primary health care unit).…”
Section: Discussionsupporting
confidence: 86%
“…A study conducted among IUCD users in Pakistan showed that 33.3% of women shifted their method of choice to short term methods [8]. Another study done in Malawi showed that 58% of woman switched to more effective method, 24% switched to similarly effective methods and 18% switched to less effective methods [9]. A study in Lusaka, Zambia showed that among 145 implant users 13% shifted the methods, from these 89% shifted to short term family planning methods.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this are inadequate exposure to contraceptives and early marriages. Nonetheless, the contraceptive use was substantially lower among women in polygamous marriages than among those in monogamous ones in Malawi (Kopp et al, 2017). The study suggests that characteristics of polygamous couples have caused polygamous women to be more resistant to birth control use than monogamous women.…”
Section: Polygamy and Contraceptive Usementioning
confidence: 80%
“…Pode ser que o preservativo masculino esteja sendo usado mais como "reforço" de outros métodos contraceptivos, ou seja, tem um caráter provisório. A mulher ou o casal, quando têm oportunidade ou necessidade, trocam esse método, e geralmente por um mais eficaz, assim como observado em outros contextos (Goldstein, Upadhyay, Raine, 2013;Kopp et al, 2017). Estudo que analisou a dinâmica da troca entre o uso do preservativo masculino e contraceptivos hormonais em mulheres que iniciaram o uso de métodos contraceptivos hormonais, observou que o uso do preservativo masculino e dos métodos hormonais ao longo do tempo foi dinâmico, e a mulher experienciou alternâncias importantes entre os dois métodos contraceptivos (Goldstein, Upadhyay, Raine, 2013).…”
Section: Descontinuidades No Uso Da Pílula Oral E Fatores Associadosunclassified
“…(Ali, Cleland, 2010b). De fato, a maior porcentagem de descontinuidade do uso do preservativo masculino é para um MAC mais eficaz (Kopp et al, 2017).…”
Section: Descontinuidades No Uso Do Preservativo Masculino E Fatores unclassified